Strategi Pembiasaan Tadarus Al-Qur’an Dalam Membangun Karakter Religius Peserta Didik Di SDN 1 Jekulo - Khasanah, Nikmatul; Nuha, Ulin (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study aims to describe the procedures for habituating Qur’an reading at SDN 1 Jekulo, analyze its role in fostering students’ religius character, and identify several faktors that support and hinder its implementation. Religius character is an important component of education, particularly in efforts to develop students with noble morals and a strong attachment to Islamic values. The habituation of Qur’an reading is considered an effective method for instilling religius values from an early age. This study employed a descriptive approach with a clear research strategy. Data were collected through observation, interviews, and documentation. The research subjects included the school principal, PAI teachers, and upper-grade students at SDN 1 Jekulo. The results show that the habituation of Qur’an reading is conducted routinely every morning before teaching and learning activities begin, with active guidance from teachers. This activity contributes to fostering students’ love for the Qur’an, improving discipline, and strengthening religius attitudes in daily life. Supporting faktors include school support and teacher involvement, while inhibiting faktors include the low motivation of some students and limited time for implementation.